Pre‐operative anaemia, intra‐operative hepcidin concentration and acute kidney injury after cardiac surgery: a retrospective observational study. (12th March 2018) - Karkouti, K.; Yip, P.; Chan, C.; Chawla, L.; Rao, V.
Summary: Acute kidney after cardiac surgery is more common in anaemic patients, whereas haemolysis during cardiopulmonary bypass may lead to iron‐induced renal injury. Hepcidin promotes iron sequestration by macrophages: hepcidin concentration is reduced by anaemia and increased by inflammation. We analysed the associations in 525 patients between pre‐operative anaemia (haemoglobin < 130 g.l −1 in men and < 120 g.l −1 in women), intra‐operative hepcidin concentration and acute kidney injury (dialysis or > 26.4 μmol.l −1 or > 50% creatinine increase during the first two days after cardiac surgery. Rates of pre‐operative anaemia and postoperative kidney injury were 109/525 (21%) and 36/525 (7%), respectively. The median (IQR [range]) intra‐operative hepcidin concentration was 20 (10–33 [0–125]) μg.l −1 and was lower in anaemic patients than those who were not: 15 (4–28 [0–125]) μg.l −1 vs. 21 (12–33 [0–125]) μg.l −1, respectively, p = 0.002. Four variables were independently associated with postoperative kidney injury, for which the beta‐coefficients (SE) were: minutes on cardiopulmonary bypass, 0.016 (0.004), p < 0.001; intra‐operative hepcidin concentration, 0.032 (0.008), p < 0.001; pre‐operative anaemia, 1.97 (0.56), p < 0.001; and Cleveland clinic risk score, 0.88 (0.35), p = 0.005. Contrary to generally increased rates of kidney injury in patients with higher hepcidin concentrations, rates of kidney injury in anaemic patients were lower in patients with higher hepcidin concentrations, beta‐coefficient (SE) −0.037 (0.01), p = 0.007. In cardiac surgical patients the rate of postoperative acute kidney injury predicted by the Cleveland risk score might be adjusted for pre‐operative anaemia and intra‐operative cardiopulmonary bypass time and hepcidin concentration. Pre‐operative correction of anaemia, reduction in intra‐operative bypass time and modification of iron homeostasis and hepcidin concentration might reduce acute kidney injury.